A REVIEW OF EXISTING CLOUD AUTOMATION TOOLS - J, Prassanna; Pawar, Anjali R; V, Neelanarayanan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Many enterprises are running distributed applications on their on-premise servers. However, if load on those servers changes unexpectedly, then it becomes tedious to scale the resources and requires skilled human power to manage such situations. It may increase the capital expenditure. Hence, many companies have started to migrate their on-premise applications to the cloud. This migration of the applications to the cloud is one of the major challenges. To setup and manage the growing complex infrastructure, after migrating these applications to the cloud are really a time-consuming and tedious process which results in downtime. Hence, we need to automate this environment. To achieve architecture for the distributed systems which support security, repeatability, reliability, and scalability, we require some cloud automation tools. This paper summarizes tools such as Terraform and cloud formation for infrastructure automation and Docker and Habitat for application automation.